EXPLORING TURKISH ARCHITECTURAL HERITAGE THROUGH FASHION: A DESIGN INSPIRED BY THE BASILICA CISTERN - Tria Astha Parameswara Putri; Indarti, Indarti (Home Economics Journal, 2025)
The historical building, Basilica Cistern, possesses strong architectural values, characterised by tall columns and a roof structure that forms geometric patterns. These architectural elements inspire the creation of an eveningwear collection. To develop textures inspired by the building, the fabric manipulation technique of surface cording is applied, offering flexibility to shape according to the design concept. To emphasise the firm architectural texture, Duchesse satin is chosen for its stiff and glossy characteristics. The combination of surface cording and duchess satin represents the geometric forms of the Basilica Cistern’s ceiling in the garment design. This study aims to examine the process of designing and producing eveningwear inspired by the Basilica Cistern’s ceiling structure through fabric manipulation using surface cording. The research applies the FEA Consumer Need Model developed by Orzada & Kallal (2021), which consists of six stages: problem identification, preliminary ideas, design refinement, prototype development, evaluation, and implementation.  This study aims to explore the architectural characteristics of the Basilica Cistern through surface cording techniques, which can be applied to other fashion designs.